P08.14.B Addressing and implementing coping strategies from pre-surgery can reduce anxiety and depression in the brain tumour population. (5th September 2022) - hurwitz, v; Lavrador, J p; La, J; ,; Brazil, L; Al-Salihi, O; Swampillai, A; Bhangoo, R; Vergani, F; Ashkan, K; Chia, K; Hedges, S; et al.
Abstract: Background: Anxiety and depression is prevalent in oncology patients and disproportionately high in neuro-oncology. The screening tools are most frequently used when signs of depression are identified later in the patients pathway. The cognitive impact of a brain tumour means coping mechanisms are harder to integrate and retain. Anti-depressants and their impact on a brain tumour have long since been debated with no clear conclusion. Implementing a programme to address the anticipatory diagnosis of anxiety and depression from first contact potentially allows patients to discuss their mental health needs more openly. Material and Methods: Patients are introduced to the concept of health related anxiety and depression following their first pre-assessment appointment, A combination of techniques are employed through different mediums including baseline assessment with EORTC QOL screening, MoCa assessment, CBT techniques, YouTube tutorials via the neuro-oncology cns channel and one to one sessions over six to nine sessions. Results: Patients perceived quality of life is higher following completion of the programme. 75% of participants were able to identify coping strategies they had learnt and how and when to use them. Oncologists reported patients were better prepared for their results and initial oncology consenting appointment. High anxiety levels caused one participant to self-discharge prior to their surgery. On completion of four sessions they returned to the hospital and underwent awake craniotomy. Conclusion: Identifying and implementing coping strategies at the earliest opportunity improves patients quality of life whilst living with a brain tumour. Anxiety and depression being discussed and the risk of developing either or both of these conditions allows for more effective prevention, awareness and diagnosis. There is the potential to further this work by looking at the impact on carers of early detection of patients anxiety and depression